Preferences for inequality: East vs. West - Marc Suhrcke (Hamburg Institute of International Economics (HWWA), 2001)
Do preferences for income inequality differ systematically between the post-socialist countries of Central and Eastern Europe and the Western established market economies? This paper analyses 1999 data from a large international survey to address this question. In particular, we examine whether attitudes to inequality differ between East and West even after the ,,conventional“ determinants of attitudes are controlled for. Results suggest that this is indeed the case. A decade after the breakdown of communism, people in transition countries are indeed significantly more ,,egalitarian“ than those living in the West, in the sense that they are less willing to tolerate existing income inequalities, even after the actual level of income inequality and other determinants of attitudes are taken into account. These results do not seem to be driven by a recent change in attitudes owing to a rapid rise in inequality during transition, but rather appear to constitute an attitudinal legacy carried over from socialism. This is very likely to have important implications for the political support of reform policy, in particular for the political feasibility of future welfare state reforms in these countries. – – Unterscheiden sich die Präferenzen für Einkommensungleichheit systematisch zwischen den Transformationsländern Mittel- und Osteuropa im Vergleich zu den etablierten Marktwirtschaften Westeuropas? Dieses Papier analysiert die Ergebnisse einer grossen internationalen Umfrage aus dem Jahre 1999. Insbesondere wird untersucht, ob sich die Einstellungen zum Thema Ungleichheit in Ost und West unterscheiden, nachdem für die ,,konventionellen“ Determinanten dieser Einstellungen kontrolliert wurde. Die Ergebnisse zeigen, dass dies in der Tat der Fall ist. Zehn Jahre nach dem Zusammenbruch des Kommunismus weist die Bevölkerung in den Transformationsländern eine signifikant ,,egalitärere“ Haltung auf als jene im Westen, insofern als sie weniger tolerant sind gegenüber gegenwärtiger Einkommensungleichheiten, selbst nachdem für das tatsächliche Niveau der Einkommensungleichheit sowie andere Einflussfaktoren kontrolliert wurde. Diese Ergebnisse scheinen auch nicht auf den relativ starken Anstieg der Ungleichheit während der Transformation zurückzuführen zu sein, sondern können eher als ein Erbe aus der sozialistischen Zeit betrachtet werden. Dies hat wesentliche Implikationen für den Grad an politischer Unterstützung zukünftiger Reformpolitik, insbesondere die politische Umsetzbarkeit von Reformen des Wohlfahrtsstaats in den Transformationsländern.
Keywords: P5; D63; D30; 330; Inequality; transition countries; attitudes; Einkommensverteilung; Soziale Ungleichheit; Öffentliche Meinung; Sozialethik; Öffentliche Meinung; Vergleich; Schätzung; Osteuropa; Westliche Welt